Tratamento da superfície do alumínio via eletrólise a plasma - Minobe, Jun Lazzarini [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This paper presents the study on the application of the electrolytic plasma for surface treatment of aluminum. A bibliographical study on the material of interest was preliminarily performed and later designed and built an electrolytic cell, including the excitation source. Unlike conventional electrolysis process, the plasma assisted carry on in the non-linear region of characteristic current/voltage curve. Therefore it requires for the on set of the process that the power supply operates on harder conditions than those on high current process. The plasma produced during the present investigation has temperatures in the range o 6,0.10 3 -7,0 .10 3 K, well above those found in conventional chemical process. It also shows a particular dynamic to promote changes on surface and to produce new materials. The plasma is generated by microdischarge in vapor or gas bubbles involved in physic-chemical processes in electrode regions of the electrolytic cell. The electrode material was the aluminum (7075). The Process Electrolytic Plasma Processing (EPP) is sensitive to various parameters such as operating voltage, current density, electrolyte, concentration of electrolyte, geometry of reactor, temperature of electrolytic solution and dynamic of the fluid in the cell. The experiments were carried on in order to find parameters for a stable abd steady operation. The choice for the electrolytic was silicate/alkali solution in various concentrations to operate in various voltage as well. Plasma was produced on negative (cathode) and positive (anode) electrode, in specific conditions. A stable operation on the cathode process was obtained with low concentration of the electrolytic in aqueous solution, current density around 250V effective voltage. For the evolution of plasma in anodic process it was required higher concentrations and higher... (Complete abstract click electronic access below)

Neste trabalho é apresentado o estudo sobre a aplicação da eletrólise a plasma para tratamento de superfícies de alumínio. Um estudo bibliográfico sobre o material de interesse foi preliminarmente realizado e posteriormente foi projetado e construído uma célula eletrolítica, incluindo a fonte de excitação. Diferente do processo da eletrólise convencional, o processo a plasma se desenvolve na região não linear da característica corrente x tensão. Requer, portanto, para a excitação do processo uma fonte de tensão que atue em patamares acima da utilizada em processos convencionais, com correntes relativamente altas. O processo em estudo produz plasmas que envolvem temperaturas da ordem de 6,0.10 3 -7,0 .10 3 K, muito acima daquelas onde ocorrem os processos químicos convencionais e, ainda apresenta uma dinâmica peculiar capaz de promover alterações nas superfícies além de produzir novos materiais. O Plasma é formado através de microdescargas em bolhas de vapor e gases envolvidos nos processos físico-químicos nas regiões dos eletrodos da cuba eletrolítica. O material de interesse, no caso alumínio (7075), constitui o eletrodo da cuba eletrolítica e sofre todo o processo físico-químico de interesse. O processo Electrolytic Plasma Processing (EPP) é sensível a diferentes parâmetros como: tensão de operação, densidade de corrente, eletrólito, da concentração de eletrólito, geometria do reator, além da temperatura da solução eletrolítica e da fluídadinâmica da solução. Experimentos foram realizados com o intuito de se encontrar os parâmetros para uma operação estável e estacionária. Optou se pelo eletrólito de silicato de sódio e variou-se a sua concentração, além da tensão de operação. Produziu-se plasma no eletrodo negativo (catodo) e também no positivo (anodo)... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Plasma (Gases ionizados); Eletrolise; Polimento eletrolitico; Espectroscopia de infravermelho; Microscopia eletronica de varredura; Ligas de aluminio; Electrolytic Plasma; Electrolysis Plasma Processing